PROPHYLACTIС DIET OF ALLERGIC DISEASES IN CHILDREN WITH HIGH RISK OF ATOPY - V.A. Revyakina; T.A. Filatova; T.E. Borovik; A.V. Gamaleeva; T.B. Sentsova; O.K. Netrebenko; A.I. Bulai (Вопросы современной педиатрии, 2007)
The preventive efficiency of various kinds of feedings in children of the first year of life with high risk of an allergic pathology is studied. Under observation there were 87 children from group of high risk of an allergic pathology (from birth up to 18 months). The results of this study have confirmed the importance of breast feeding for prophylaxis of an allergic pathology in children with high risk of atopy. If it is impossible, the transclation of the child on artificial feeding by an dairy admixture based on a partial hydrolysate of serumal protein, which procvides physiological needs of a growing organism, assists physiological dynamics of parameters of weight and height, allows to increase frequency of early manifestation of atopy and prevents a sensibilization to proteins of the cow milk.Key words: allergic diseases, prevention, feeding, hydrolysate of protein of the cow milk, infants.